Thoracoabdominal Diseases: Diagnosis and Management from the Root to the Renals - Vinall, Maria (MD Conference Express, 2009)
This article discusses considerations for deciding on surgical intervention for aortic root endocarditis must be a reasonable prospect of recovery with satisfactory quality of life. It also looks at traditional and evolving management strategies for thoracoabdominal dissections.